النص و الظواهر اللغوية قراءة في فكر ابن جني اللغوي: The text and linguistic phenomena through Ibn Jinni’s linguistic thought - Ahmad Eldesoky, Ebrahim Mohammed (SIBAWAYH Arabic Language and Education, 2020)
This research seeks to describe some of the language phenomenon if it is different or agree with the text. The explanation should be linked with its semantic aspect in the text. This is derived from some of the books of Ibn Jinni may god rest his soul a. And to reveal if the use of contrary grammatical phenomenon is a matter of linguistic necessity. This research came in the introduction, three chapters and conclusions as follows, the first chapter title is Ibn Jinni. The second chapter title is the linguistic phenomena between sculptors and rhetoricals. The third chapter title is Ibn Jinni and the role of the text in the interpretation of linguistic dahaler phenomena. This research with adopt the descriptive methodology.